MATHEMATICAL MODEL OF SYMMETRIC VIBRATOR - METELYTSYA, ARTEM; KOVALENKO, VIKTOR; TROMSIUK, VOLODYMYR; FORMANCHUK, MYKOLA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
In the work, theoretical and experimental studies of the mathematical model of the value of the power flux density of the wave symmetric vibrator in the near zone were carried out using the MMANA-GAL software package. The density and structure of the field of an elementary electric emitter in the near zone have been determined. Directional diagrams of a half-wave symmetric vibrator with wavelengths of 0.5λ, λ, and 100λ were constructed. The directionality of electromagnetic wave radiation is of great importance in radio communication technology. The directionality of radiation can be ensured if the size of the antenna significantly exceeds the length of the emitted or received wave. The development of portable antennas for mobile phones is determined by two main aspects – acceptable broadband and maximum uniformity of electromagnetic radiation along the azimuthal angle with a high amplification factor. These conditions contradict the fact that the antenna is raised close to the human head with a wavelength comparable to the wavelength. During telephone conversations, the subscriber's head absorbs and scatters the electromagnetic energy emitted by the antenna, so that the meridional uniformity of the radiation is disturbed. The proposed mathematical model of the value of the power flow density of the wave symmetric vibrator in the near zone allows us to reduce the impact of the electrical component on human health. Such conclusions were drawn based on the results of simulation modeling of a half-wave symmetric vibrator using a synthesized mathematical model for the power flux density of a symmetric wave vibrator in the near zone in the MMANA-GAL environment, taking into account the fact that the direction of electric and magnetic radiation changes by 90 degrees with an increase in wavelength. The results of the study can be used for the development of effective antennas to reduce the negative impact on human health, in particular on the functioning of the brain.
Keywords: symmetric vibrator; electric field component; directional diagram